Garden allies : the insects, birds, & other animals that keep your garden beautiful and thriving - Lavoipierre, Frédérique (Timber Press, 2021)
An illustrated guide to the animals and insects that live in our yards and gardens and act as helpful friends by pollinating and keeping pests in check and includes information on welcoming and nurturing these creatures.